Open Monograph Press dalam Mendukung Visibilitas, Indeks, dan Sitasi Buku Ilmiah Elektronik Akses Terbuka - Mahelingga, Dhevi Enlivena Irene Restia (UI Scholars Hub, 2022)
This study tries to provide an overview of how open access scientific books from the OMP-based website at LIPI Press contribute to supporting the means of disseminating knowledge. This study used a descriptive qualitative method with data collection through literature study and observation of the OMP LIPI Press system, Google Analytics, Google Scholar, and Dimensions. The application of OMP as a scientific publishing system provides many benefits, not only in facilitating the editorial flow of publishing, but also in supporting the impact of electronic scientific books in the form of indexes and citations as well as visibility of the institution's website domain. Based on the research results, the OMP system is recommended to become the standard for scientific publishers, both R & D institutions and universities. This urgency is especially for books from research that are funded by public, whose usefulness should be felt by the wider community through open access. The ease and potential of OMP in supporting the impact of electronic scientific books is expected to catch up with OJS which has become the standard for publishing electronic scientific journals in Indonesia.